2016
DOI: 10.4338/aci-2015-11-ra-0165
|View full text |Cite
|
Sign up to set email alerts
|

Applying Electronic Medical Records in health care

Abstract: KeywordsElectronic medical record (EMR), physician, technology acceptance model (TAM), diffusion of innovation theory (DOI), structural equation modeling (SEM) SummaryBackground: In order to fulfill comprehensive interoperability and recognize the electronic medical records (EMRs') benefits, physicians' attitudes toward using and applying EMR must be recognized. Objectives: The purpose of this study was to present an integrated model of applying EMRs by physicians. Methods: This was a cross sectional study in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 36 publications
(62 reference statements)
8
42
0
Order By: Relevance
“…Some studies carried out by some researchers in order to find any possible relationship. They came to this conclusion that association among them is negative and direct which implies that the more the mobile technology services become complicated, the less they are used by the people 2,[23][24][25]29,30 . This research showed that there is no association among them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies carried out by some researchers in order to find any possible relationship. They came to this conclusion that association among them is negative and direct which implies that the more the mobile technology services become complicated, the less they are used by the people 2,[23][24][25]29,30 . This research showed that there is no association among them.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with other studies already done in the field like 2, 7, 9, 23,24 . The literature indicated positive and significant effect of relative advantage on both PU and PEOU, the researchers implied that the users would be more delighted to implement mobile technology at their work if it had some sort of relative advantage 2,6,17,[25][26][27] . Concerning this association, H6 was supported in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Additionally, PSQ were studied and noted as having a relationship with concepts described in the TAM model. 19 Most studies have focused on health professionals' behavioral intention to use health care technology. 20,21 Holden and Karsh highlighted the necessity of contextualizing the TAM model for health care settings and suggested that this could be done by differentiating between performance benefits accruing at the personal and group levels, focusing on health care outcomes, and allowing for different sources of social influences.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…29,30 Interoperability issues may arise if patient care requirements, clinical processes, and administrative requirements are not adequately addressed. 19,31 Interoperability refers to the ability of various information systems and software applications to communicate, exchange data, and use information that has been exchanged. 32 Definitions for e-prescriptions contain the use cases, requirements and data contents of the pharmacy system, Patient Records Archive, and HL7 definitions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%